Petrogenesis and tectonic setting of Triassic granitoids in the Qiangtang terrane, central Tibet: Evidence from U-Pb ages, petrochemistry and Sr-Nd-Hf isotopes - Li, G.; Li, J.; Zhao, J.; Qin, K.; Cao, M.; Evans, Noreen (Elsevier Ltd, 2014)
Triassic granitoids, including the ~220Ma Shuanghu and ~210Ma Rongma granitoids studied here, are widely distributed around the Longmu-Shuanghu suture and in the Qiangtang terrane, central Tibet. The majority of these granitoids can be classified as high-K calc-alkaline in nature and yield negative Ba and Sr anomalies on primitive mantle-normalized diagrams. In addition, they are: enriched in light rare earth elements (LREE) ((La/Yb)N =1.61-21.79); strongly enriched in large ion lithophile elements (LILE: e.g., Cs, Rb, and K), and depleted in high field strength elements (HFSE: e.g., Nb and Ti). Magma mixing played a role in the genesis of the Shuanghu granodiorites, as indicated by the occurrence of dioritic enclaves and the wide range in zircon Hf compositions (eHf(t)=-15.0 to -2.5). The I-type Shuanghu granodiorites and S-type Shuanghu and Rongma granites might have been derived from melting of southern Qiangtang crust given the high initial Sr (0.7131-0.7272), low eNd(t) (-8.9 to -11.1) and zircon eHf(t) values (-15 to -7.2). The granitoids may have formed during melting of southern Qiangtang crust, heated by upwelling asthenosphere mantle, a result of break-off and delamination of the Paleo-Tethys slab in a collisional setting.